Carbon Labeling and Poor Country Exports - Brenton, Paul (World Bank, Washington, DC, 2012)
Carbon labelling is being adopted by private firms as a mechanism for mitigating climate change. Such schemes are likely to have a significant impact on low-income country exports due to the need for transportation and the small size of their exporters. However, transport emissions may be offset by favorable production conditions and size bias may be reduced. The design and implementation of carbon labelling will need to take into account a number of complex, technical challenges. As innovative solutions emerge, it is important that low income countries are involved in discussions on the design and implementation of carbon labelling.